Fire history and growth response of chir pine (pinus roxburghii sarg.) under influence of wild fires and climate in Kamichu Daga, Wangdue Phodrang - Lham Tshering (CNR, Lobesa Lham Tshering, 2022)
includes acknowledgement and abstract
Keywords: BSc Thesis